Correlation between astrocyte activity and recovery from blood–brain barrier breakdown caused by brain injury. Issue 12 (17th August 2016) - Ikeshima-Kataoka, Hiroko; Yasui, Masato
Abstract : Glial activation is associated with cell proliferation and upregulation of astrocyte marker expression following traumatic injury in the brain. However, the biological significance of these processes remains unclear. In the present study, astrocyte activation was investigated in a murine brain injury model. Brain injury induces blood–brain barrier (BBB) breakdown and immunoglobulin G (IgG) leak into the brain parenchyma. The recovery of BBB breakdown was evaluated by analyzing immunofluorescent staining with mouse IgG antibody. IgG leakage was greatest at 1 day after stab wound injury and decreased thereafter, and almost diminished after 7 days. Bromodeoxy uridine incorporation was used, and astrocyte proliferation rates were examined by coimmunostaining with anti-bromodeoxy uridine and anti-glial fibrillary acid protein antibodies. Consistent with IgG leakage assays, astrocyte activation was the highest at day 3 and decreased after 7 days. Moreover, in reverse transcriptase-quantitative-PCR experiments, genes associated with BBB integrity were downregulated immediately after BBB breakdown and recovered to basal expression levels within 7 days. These data indicated that astrocyte activation correlated with BBB recovery from breakdown following brain injury.